Enviromental management and concept during construction of dam: A study case of Murum dam, Belaga District, Kapit Division, Sarawak - Michael, Castro (Universiti Malaysia Sarawak (UNIMAS), 2013)
Dam is physical barrier that was constructed purposely to impound water or underground streams, which serve the primary purpose of retaining water. It can be also use as floodgates or levees to manage or prevent water flow into specific land regions. This study is focusing on documentation of the environmental management, legislations and guidelines, and water quality analysis. Documentation such as EIA study report is mandatory as accordance to Malaysia legislation. Therefore, strict enforcement should be carried out to regulate existing legislation and also to monitor impacts from the dam's development. Water quality sampling was carried out at Murum River and its tributaries at six sampling locations. Results of the water quality analysis showed parameters such as BOD5, COD, TSS, turbidity, ammoniacal nitrogen and total coliform count exceeded the National Water Quality Standards for Malaysia (NWQS) compliance limit indicating the large number of workers population at the dam site as the main contributing factor. Pollutants are mostly from sewage discharge, soil erosion and decomposing organic materials.